Особенности постколониального метадискурса в эссеистике Евгения Маланюка - Poddenezhna, Olena (Studia Rossica Posnaniensia, 2025)
The article analyzes the postcolonial metadiscourse of the essays by Yevhen Malaniuk, a prominent representative of the Ukrainian diaspora. It examines a series of his articles, which deconstruct established historical and cultural narratives of Russian literature, revealing elements of colonial trauma and myth-making. The research demonstrates that Malaniuk transcends traditional essayism, actively participating in the decolonization of the cultural space. In his interpretation, Russian literature becomes a symbol of imperial power. However, his authorial strategy is not limited to unambiguous criticism or approval; he aims to deeply understand and objectively present the creative systems of Russian writers, offering a complex multi-level evaluation of their work and assessing the forms of their influence on the formation of cultural identity. His analytical gaze is aimed at demystifying canonical views of Russian literature. Malaniuk approaches literature as a platform through which personal cultural concepts, ethnological patterns, and socio-political attitudes are expressed. His interpretation of the Ukrainian theme through the prism of postcolonial theory affirms the significance of an approach that combines postcolonialism and post-communism in their efforts to demystify dominant narratives of the past and to explore the nature of individual and collective memory, as well as mechanisms of resistance to authoritarianism. The article thoroughly analyzes Malaniuk's thesis on the national criterion in art, which asserts that in the postcolonial era, the emphasis on the national criterion helps restore unique cultural identities that have been degraded during the colonial period. The article argues that one of the constant criteria for forming the methodological base of postcolonial interpretation becomes a nation-centric evaluation. This argument turns into an act of cultural and political resistance, facilitating the revival of identity and dismantling the canon of conservative views regarding categories such as nation, people, culture, personality, society, and educates the reader to newly comprehend this complex of ideas, now dictated by the newest times.